S100 Novel T helper cell responses against Pseudomonas aeruginosa in healthy individuals and patients with cystic fibrosis. (14th November 2013) - Bayes, HK; Brodlie, M; Ward, C; Corris, PA; MacGregor, G; Bicknell, S; Evans, T
Abstract : Introduction and Objectives: Pseudomonas aeruginosa (PA) colonisation is a hallmark of cystic fibrosis (CF) resulting in damaging neutrophilic inflammation. Patients with CF produce anti-pseudomonal antibodies but the role of CD4 + T cell responses to PA remains unclear. Novel T helper cell subsets, Th17 and Th22 cells, have important roles in host defense but may also enhance tissue damage. We aimed to define the antigen-specific memory T helper cell responses to Pseudomonas aeruginosa in healthy humans and patients with cystic fibrosis. Methods: CD14 + monocytes and memory CD4 + CD45RO + T cells were isolated from peripheral blood of CF patients with PA colonisation (n = 8) and healthy controls (n = 10). Monocyte-derived dendritic cells (DCs) were stimulated with live Pseudomonas strain PA103 and PA isolates derived from CF patients. Autologous T cells were co-cultured with activated DCs. The resultant T helper response was determined by measuring proliferation, immunoassay of cytokine output, and immunostaining of intracellular cytokines. Lavage samples from explanted CF lungs were assayed for IL-22 secretion. Results: Healthy individuals andpatients with cystic fibrosis had robust antigen-specific memory CD4 + T cell responses to Pseudomonas aeruginosa that not only contained a Th1 and Th17 component but also Th22 cells. In contrast to previous descriptions of human Th22 cells, these Pseudomonal-specific Th22 cells lacked the skin homing markers CCR4 or CCR10, although they did express the chemokine receptor CCR6 that would direct migration to damaged epithelial surfaces. Furthermore, IL-22 production was evident in the lungs of CF patients colonised with PA. Healthy individuals and patients with cystic fibrosis had similar levels of Th22 and Th1 cells, but the patient group had significantly fewer Th17 cells in peripheral blood. Conclusions: MemoryTh22 cells specific to Pseudomonas aeruginosa are induced in both healthy individuals and patients with CF, with IL-22 secretion being demonstrated in the CF lung. These Th22 cells do not express tissue specificity for gut or skin sites and we thus hypothesise may have a role in respiratory defense. Along with Th17 cells, they may play an important role in the pathogenesis of pulmonary infection with this microbe in patients with cystic fibrosis.